Increased Activation of Default Mode Network in Early Parkinson’s With Excessive Daytime Sleepiness - Ooi, Leon Qi Rong; Wen, Ming-Ching; Ng, Samuel Yong-Ern; Chia, Nicole Shuang-Yu; Chew, Isabel Hui Min; Lee, Weiling; Xu, Zheyu; Hartono, Septian; Tan, Eng King; Chan, Ling Ling; Tan, Louis Chew-Seng (Frontiers in Neuroscience, 2019)
Background and Objectives: The underlying neuropathology of excessive daytime sleepiness (EDS) remains elusive in Parkinson’s disease (PD). We aim to investigate neural network changes that underlie EDS in PD. Methods: Early PD patients comprising eighty-one patients without EDS (EDS-) and seventeen patients with EDS (EDS+) received a resting state functional MRI scan and the Epworth Sleepiness Scale(ESS). Connectivities within the default mode network(DMN), motor and basal ganglia networks were compared between the EDS+ and EDS- groups. Correlations between network connectivity and the severity of EDS were investigated through linear regression. Results: EDS+ patients displayed a trend of increased network connectivity of the posterior DMN (pDMN). A significant positive correlation was found between connectivity of the ventromedial prefrontal cortex in the pDMN and ESS. Conclusion: EDS+ patients are likely to display increased activation in the DMN, suggesting neural compensation in early PD or impaired attentiveness due to mechanisms such as mind-wandering.